Model Development of Android-Based Learning in Vocational High School - Elida; Dony Novaliendry; Noper Ardi; Erni Marlina Binti Saari; Nurindah Dwiyani (International Journal of Interactive Mobile Technologies (iJIM), 2023)
This study aimed to develop an Android-based learning model for subjects of Creative Products and Entrepreneurship for catering students at Vocational Schools. The study analyzed the validity of Android- based learning models and analyzed practicality and the effectiveness of Android-based learning models for Creative Product and Entrepreneurship subjects for catering students at SMK Negeri 9 Padang. Based on the validity assessment of material experts, media experts, linguists, and practitioners, the average score of material aspects is 4.78 (Very Eligible), the media aspect is 4.22 (Very Eligible), and the language aspect is 4.23 (Very decent). The results of practicality tests for teachers and students, as well as the effectiveness test of the use of Android-based learning media on students of Creative Product and Entrepreneurship subjects conducted using a questionnaire, obtained a practicality value of 4.55 (feasible) and effectiveness of 4.62 (feasible).